PENGELOLAAN WAKAF PRODUKTIF UNTUK KESEJAHTERAAN MASYARAKAT DI DESA SUMBERBENING (Studi Kasus MWC NU Kecamatan Balerejo Kabupaten Madiun) - Itmi, Desi; SJ, Ahmad Syafi'i; Nafiah, Nafiah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Waqf is a form of Muamalah Maliyah (property) which has long been known by the community for a long time. Excess assets owned by a person, should be a positive tool that can be used in social interaction to help each other and help each other. Regarding the issue of waqf, the government seriously issued Law Number 41 of 2004 concerning Waqf to become the momentum to realize waqf productively, because in this Law, waqf contains a very broad dimension, covering immovable assets including cash waqf, not limited to establishments places of worship and social religion. In the Balerejo sub-district, the management of productive waqf is still very minimal. Broadly speaking, the management of waqf is only used for places of worship. This fact has become an encouragement for the MWC NU Balerejo sub-district in developing the economic development of the people through waqf assets. So the MWC NU Balerejo is trying to manage a plot of land waqf in Sumber Bening Village which was originally in the form of paddy fields for the construction of MWC buildings and minimarkets in order to empower the waqf land to become productive waqf land for the welfare of the community. in Sumberbening Village, Balerejo District, Madiun Regency (2) What are the driving and inhibiting factors for productive waqf management in Sumberbening Village, Balerejo District, Madiun Regency. This research was conducted qualitatively with observation, interview and documentation procedures. Based on data analysis it was concluded that the productive waqf management mechanism of MWC NU Balerejo is by collecting assets (capital), productive and developing waqf assets and the last is distributing the waqf proceeds to the community. In order to achieve waqf management that provides benefits for improving the welfare of the community, especially business actors, orphans, the poor and the dhuafa. Factors supporting the management of this waqf are the existence of professional nazirs in managing productive waqf, while the inhibiting factors are the lack of public understanding of waqf, geographical factors and lack of support costs.